A modified Hilbert fractal resonator based rectenna design for GSM900 band RF energy harvesting applications. Issue 1 (14th January 2019) - Palandoken, Merih; Gocen, Cem
Abstract: This article proposes a novel rectenna design based on modified Hilbert fractal shaped microstrip antenna and Villard voltage doubler rectifying circuit for RF energy harvesting applications operating at Global System for Mobile Communications (GSM) 900 MHz band. The energy harvesting antenna is numerically optimized and fabricated on a Rogers RO4003 substrate of thickness 1.52 mm with a compact overall physical sizes of 80 mm × 82 mm ( λ 0 /4.16 × λ 0 /4.06). Various geometric parameters and circuit component values of the proposed energy harvesting system are optimized in order to achieve a matched input impedance with good radiation performance of high gain for the input power level less than −20 dBm. The numerical and experimental results point out the technical potential of the proposed rectenna design to be utilized in DC power supply modules of low voltage, low power electronic devices.